An Indian logic-based knowledge-sharing architecture for virtual knowledge communities. (6th February 2009) - Mahalakshmi, G.S.; Karpagaraj, M.; Geetha, T.V.
This paper discusses autonomous Knowledge Sharing (KS) among a collection of KS volunteers, called the virtual knowledge community. The KS protocol determines the inclusion/exclusion of knowledge volunteers and regulates the discussion within the community. The entire autonomous discussion takes place with the initial predicates of world knowledge ontology represented in Indianised Logics. During discussion, the proponent refers to the invariable concomitance relation between the relating concepts to explain the inference to other opponents. The knowledge volunteers are grouped according to a degree of trust, based on which the proposed knowledge is either accepted or rejected. Therefore, by rationally exchanging questions and answers in a debate fashion, knowledge is explored and a definite conclusion is reached at the end of the discussion, irrespective of the winning/losing of the individual arguments. In this fashion, autonomous knowledge volunteers gain new and valid knowledge, using which they arrive at new conclusions in the future.